1986
DOI: 10.1002/app.1986.070320611
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of 1‐hexene polymerization

Abstract: SynopsisKinetics of 1-hexene polymerization was studied by following the amount of unreacted monomer using gas chromatography. The Ziegler-Natta catalyst system used was comprised of TiC1,-AlEt, with A1 : Ti ratio of 0.85. The sampling and monomer analysis techniques developed can be applied to study the kinetics of higher a-olefins polymerizations, in general. Also, with minor modifications in this technique, a precise profile of molecular weight can be obtained during polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Therefore, it was expected that oil-soluble polymers would be a more likely candidate to dissolve in supercritical CO 2 compared to water-soluble polymers. Heller et al identified 18 hydrocarbon-type polymers that exhibited encouraging solubility (0.22-10 g/litre) in CO 2 at pressures of 11.7-21.4 MPa and temperatures of 293-331 K [9][10][11][12][13][14]. Although several polymers showed a slight increase in CO 2 viscosity, none of the studied polymers were capable of enhancing the viscosity of CO 2 significantly to a useful level.…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 99%
“…Therefore, it was expected that oil-soluble polymers would be a more likely candidate to dissolve in supercritical CO 2 compared to water-soluble polymers. Heller et al identified 18 hydrocarbon-type polymers that exhibited encouraging solubility (0.22-10 g/litre) in CO 2 at pressures of 11.7-21.4 MPa and temperatures of 293-331 K [9][10][11][12][13][14]. Although several polymers showed a slight increase in CO 2 viscosity, none of the studied polymers were capable of enhancing the viscosity of CO 2 significantly to a useful level.…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 99%
“…The displacement efficiency is very high where the " C02 actually contacts the oil, but by fingering the C02 bypasses most of the petroleum in the formation. Petroleum engineers have tried for decades to design an additive [11] that can raise the viscosity of carbon dioxide (at low concentration) to a level comparable to the oil being displaced, thereby inhibiting the formation of "fingers". Success, unfortunately, has been elusive.…”
Section: Introductionmentioning
confidence: 99%